A reconnaissance provenance study of Triassic–Jurassic clastic rocks of the Russian Barents Sea. (2nd October 2019) - Khudoley, Andrey K.; Sobolev, Nikolay N.; Petrov, Eugene O.; Ershova, Victoria B.; Makariev, Alexander A.; Makarieva, Elena V.; Gaina, Carmen; Sobolev, Peter O.
ABSTRACT: Combined U–Pb detrital zircon dating of 21 samples, along with whole-rock chemical composition and Sm–Nd isotopic studies of 39 samples of Triassic and Jurassic rocks from Franz Josef Land and wells in the southern part of the Russian (eastern) Barents Sea, were analyzed for a reconnaissance provenance study. The similarity of detrital zircon age distributions was statistically assessed using the Kolmogorov–Smirnov (K–S) test and points to a common source area for the clastic material of Triassic to Middle Jurassic age. Uralian-age detrital zircons predominate in all samples, with a comparably smaller portion of Caledonian- and Timanian-age detrital zircons. The number of Palaeoproterozoic and Archean grains is very small and becomes significant only in a few Jurassic samples. εNd (t) values gradually decrease from −1.5 to +2.5 in Lower Triassic rocks, to −2.0 to −8.2 in Jurassic rocks, suggesting an increasing influence of ancient metamorphic basement erosion in the younger Jurassic rocks. High Co/Th ratios, suggesting the erosion of mafic rocks, were mainly recorded in Lower Triassic rocks, whereas increasing Th/Sc ratios, suggesting the erosion of felsic rocks, were recorded only in some uppermost Triassic and Jurassic rocks. We identify the Urals and, in addition during the Triassic, the basement of the West Siberian Basin as the main provenance for the studied clastic rocks. By contrast, only a small volume of fine-grained clastic detritus was derived from basement erosion of the East European Craton, which was characterized by a subdued relief during this time.